2009
DOI: 10.1253/circj.cj-08-0995
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Noncompaction

Abstract: Left ventricular noncompaction (LVNC) is a recently defined cardiomyopathy characterized by a pattern of prominent trabecular meshwork and deep intertrabecular recesses, and is thought to be caused by arrest of normal endomyocardial morphogenesis. Although LVNC has been classified as a primary cardiomyopathy of genetic origin, its definition and diagnostic criteria are still being debated. Isolated LVNC was thought to be rare; however, heightened awareness has resulted in an increased detection of the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
116
0
7

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 63 publications
1
116
0
7
Order By: Relevance
“…Left ventricular noncompaction is a genetically heterogeneous condition that occurs because of failure of normal myocardial maturation during cardiac embryogenesis (Chin et al 1990;Ichida 2009) and results in prominent trabeculations, particularly in the left ventricle (Chin et al 1990;Ichida. 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left ventricular noncompaction is a genetically heterogeneous condition that occurs because of failure of normal myocardial maturation during cardiac embryogenesis (Chin et al 1990;Ichida 2009) and results in prominent trabeculations, particularly in the left ventricle (Chin et al 1990;Ichida. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are several genes associated with isolated LVNC including G4.5 (TAZ), dystrobrevin (DTNA), LIM domainbinding protein 3 (Cypher/ZASP: LDB3), Lamin A/C (LMNA), SCN5A, and sarcomere proteins (b-myosin heavy chain, a-cardiac actin (ACTC), cardiac troponin T [TNNT2], tropomyosin 1 [TPM1]) (Xing et al 2006;Ichida 2009;Chang et al 2011). These gene products have functions related to cytoskeletal and/or mitochondrial function (Tang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of cases have been observed in asymptomatic individuals. Although described as rare until recently (with a prevalence in adults estimated at 0.014%) 3 , recent studies have suggested that it is underdiagnosed: in a recently published study, almost 25% of the patients referred to a Heart Disease Clinic who presented LV systolic dysfunction met the criteria for this diagnosis 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular noncompaction (LVNC) represents arrest of the normal process of myocardial compaction process and results in the persistence of multiple prominent ventricular trabeculations and deep intertrabecular recesses (Ichida 2009). The clinical presentation and natural history of LVNC are highly variable, ranging from no symptoms to disabling congestive heart failure, arrhythmias, and systemic thromboemboli (Ichida 2009).…”
mentioning
confidence: 99%
“…The clinical presentation and natural history of LVNC are highly variable, ranging from no symptoms to disabling congestive heart failure, arrhythmias, and systemic thromboemboli (Ichida 2009).…”
mentioning
confidence: 99%